Aqueous-phase room-temperature afterglow crystalline micro/nanostructures via supramolecular inclusion complexation of γ-cyclodextrin with difluoroboron β-diketonate luminescence compounds - Qianqian Yan; Junbo Li; Tengyue Wang; Wen Xia; Guangming Wang; Haodong Li; Kaka Zhang (Next Materials)
Room-temperature phosphorescence and organic afterglow materials exhibit significant applications in diverse fields. Among them, aqueous-phase organic afterglow materials display interesting biomedical and other applications, whereas afterglow material fabrication in aqueous medium remains less explored when compared to those in solid states. In view of the excellent afterglow performance in difluoroboron β-diketonate containing systems, here we report supramolecular inclusion complexation of γ-cyclodextrin (γCD) with difluoroboron β-diketonate (BF2bdk) phosphors for devising aqueous-phase room-temperature afterglow crystalline micro/nanostructures. The γCD-BF2bdk host-guest supramolecular interactions induce crystallization of the two-component system into micro/nanostructures where BF2bdk’s triplet excited states can be well protected from nonradiative decay and oxygen quenching, leading to the emergence of aqueous-phase afterglow with phosphorescence lifetimes around 1 s and high photoluminescence quantum yields (PLQY) > 50 %. The aqueous afterglow materials possess visible-light-excitable property and can serve as donor of energy transfer for constructing long-wavelength and color-tunable afterglow systems. Their potential applications for bioimaging were further demonstrated. The present study provides a simple method but a new avenue for the preparation of high-performance aqueous-phase afterglow materials.